2015
DOI: 10.1002/wene.167
|View full text |Cite
|
Sign up to set email alerts
|

Review of catalytic syngas production through steam or dry reforming and partial oxidation of studied liquid compounds

Abstract: Although natural gas is the main feedstock for the production of hydrogen and syngas, liquid hydrocarbons and oxygenated compounds are of interest for reasons associated with their local availability and their easiness to be stored and transported. This review focuses on steam, dry, and partial oxidation of liquid feedstock. The vast research work published in these fields does not allow for a full coverage of the entire literature. Instead, the authors present from both scientific and technical stand points t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 82 publications
(129 reference statements)
1
31
0
Order By: Relevance
“…The stability test was carried out on 10 wt % Ni/CeO 2 -Al 2 O 3 catalysts at 750 • C for 30 h with a GHSV of 40,000 mL g −1 h −1 . Under these conditions, the formation of carbon nanotubes was confirmed from scanning electron microscopy (SEM) scans, however it was believed that it has no impact on the stability, and hence, the improved stability of CeO 2 was attributed to the suppression of graphite-like carbons confirming previous findings for CeO 2 -modifed SiO 2 [20] and CeO 2 modified MgO-Al 2 O 3 [21]. To further understand these observations, in-situ XRD and H 2 -TPR were conducted to gain more insights into the structural evolution of the catalyst and correlate the CeO 2 -Al 2 O 3 mixed oxide catalyst with the catalytic performance.…”
Section: Effects Of the Support On The Catalytic Activity In Drmsupporting
confidence: 77%
See 2 more Smart Citations
“…The stability test was carried out on 10 wt % Ni/CeO 2 -Al 2 O 3 catalysts at 750 • C for 30 h with a GHSV of 40,000 mL g −1 h −1 . Under these conditions, the formation of carbon nanotubes was confirmed from scanning electron microscopy (SEM) scans, however it was believed that it has no impact on the stability, and hence, the improved stability of CeO 2 was attributed to the suppression of graphite-like carbons confirming previous findings for CeO 2 -modifed SiO 2 [20] and CeO 2 modified MgO-Al 2 O 3 [21]. To further understand these observations, in-situ XRD and H 2 -TPR were conducted to gain more insights into the structural evolution of the catalyst and correlate the CeO 2 -Al 2 O 3 mixed oxide catalyst with the catalytic performance.…”
Section: Effects Of the Support On The Catalytic Activity In Drmsupporting
confidence: 77%
“…The XRD diffraction patterns of the 10 wt % Ni/CeO 2 -Al 2 O 3 catalyst is shown in Figure 2. It can be clearly observed that the calcined catalyst at room temperature, characteristic peaks were detected for CeO 2 , and X-ray Photoelectron Spectroscopy (XPS), were deployed to investigate the nature of the coke deposited on the spent catalysts. Two peaks were observed in the derivative TGA profile, with the low temperature peak corresponding to reactive carbon, whereas the high temperature peak represents a more crystalline coke.…”
Section: Effects Of the Support On The Catalytic Activity In Drmmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods such as carbon capture and storage, energy efficiency and conservation, negative CO2 emission and catalytic reforming of methane have been explored to mitigate greenhouse effect [2][3][4]. Among these options, The production of syngas with unity molar ratio is theoretical favored by methane dry reforming, hence the suitability of the syngas as chemical intermediates for the production of oxygenated fuels [7]. However, one of the major constraints with the methane dry reforming is catalyst deactivation via sintering and cooking due to the highly endothermic nature of the reaction [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, they deactivate relatively quickly owing to C deposition and sintering. Noble metals, such as Rh, Ru, Pt and Pd, are also employed and display better resistance to deactivation for comparable activity with Ni but they are much more expensive [28]. To improve the resilience of Ni catalysts to C deposits, promotors like alkali metals are used as they enhance steam adsorption [29].…”
Section: Introductionmentioning
confidence: 99%